PROFESIONALISME KONSELOR SEKOLAH DALAM PELAYANAN GENERASI MILENIAL - Sholihah, Isna Ni'matus; Handayani, Titin; Baskoro, Bambang Tejo (Jurusan Bimbingan dan Konseling, 2019)
Profession has a code of ethics in the form of a behavior regulation tool for the caretaker of the profession. This regulation guarantees that services will be carried out professionally. School counselors face an exciting challenge of serving the millennial generation. This generation is a technology reliant, image driven, multitasking, open to change, confident, team oriented, rich of information, impatient and adaptable. Guidance and counseling services need to adapt the virtual concept, in this case digital services through social media for maximum service and reference.